IDENTIFICATION OF POTENTIAL HAZARDS AND RISKS IN THE CRUDE PALM OIL INDUSTRY USING FTA, ETA, FMEA, AND SHERPA METHODS (CASE STUDY: GRADING â CLARIFICATION PRODUCTION PROCESS AT PT. X, JAMBI) - Atha Tifalni Yanuar, Ulfi
PT X is one of the Crude Palm Oil Industries (CPOI) in Jambi Province that experienced 5 (five) work accident cases from 2021 to 2023. This research aims to identify potential hazards and risks in the production process of PT X, which includes the grading and sorting station, boiling, pressing, stamping, refining, boiler, and workshop. The method for identifying potential hazards and risks uses Fault Tree Analysis (FTA) to identify the root causes of five workplace accidents at PT X, Event Tree Analysis (ETA) to determine potential hazards that may occur, Failure Mode Effect Analysis (FMEA) to identify the most risky potential hazards based on the Risk Priority Number (RPN), which is the result of multiplying severity, occurrence, and detection. Then, the RPN is categorized into low risk (RPN ? 50), medium risk (RPN = 51-100), high risk (RPN ? 101-200), and very high risk (RPN ? 201), and the Systematic Human Error Reduction and Prediction Approach (SHERPA) identifies potential human error hazards based on the work steps in a production process. This study shows that the results of the FTA analysis identified the root cause of 5 (five) workplace accidents at PT X, which is generally due to insufficient management control in the implementation of occupational health and safety (OHS). The results of the ETA analysis identified potential hazards that could occur at PT X, including being injured by sharp tools in the grading and sorting area, being hit by a forklift or transport equipment, falling or slipping in the refining area, being burned by hot surfaces, and being struck by fruit or palm bunches from the conveyor. The results of the FMEA analysis indicate that the highest RPN of 318.9 is related to machine noise during the pressing process, while the lowest RPN of 21.6 is related to tripping over materials in the threshing process. The most dominant type of action error is 67 action errors (52.75%), followed by 39 checking errors (30.70%), 11 retrieval errors (8.66%), and 10 information errors (7.8%). Recommendations for controlling and improving potential hazards in the production process include substitution, engineering controls, administrative controls, and personal protective equipment.